Evolution and controlling factors of the gravity flow deposits in the Miocene sequence stratigraphic framework, the Lower Congo—Congo Fan Basin, West Africa - CHEN, Hua; LIN, Changsong; ZHANG, Zhongmin; ZHANG, Demin; LI, Ming; WU, Gaokui; ZHU, Yixuan; XU, Hai; LU, Wenming; CHEN, Jihua (Petroleum exploration and development, 2021)
To understand the evolution of the Miocene gravity flow deposits in the Lower Cong—Congo Fan Basin, this paper documents the Miocene sequence stratigraphic framework, the depositional characteristics and the controlling factors of the gravity flow system. Based on the establishment of high-resolution sequence stratigraphic framework, lithofacies characteristics and sedimentary units of the gravity flow deposits in the region are identified by using seismic, well logging and core data comprehensively, and the sedimentary evolution process is revealed and the controlling factors are discussed. The Miocene can be divided into four 3rd-order sequences (SQ1—SQ4). The gravity flow deposits mainly include siliciclastic rock and pelite. The main sedimentary units include slumping deposits, mass transport deposits (MTD), channel fills, levee-overbank deposits, and frontal lobes. In the Early Miocene (SQ1), mainly gull-wing, weakly restricted to unrestricted depositional channel-overbank complexes and lobes were formed. In the early Middle Miocene (SQ2), W-shaped and weakly restricted erosional-depositional channels (multi-phase superposition) were subsequently developed. In the late Middle Miocene (SQ3), primarily U-shaped and restricted erosional channels were developed. In the Late Miocene (SQ4), largely V-shaped and deeply erosional isolated channels were formed in the study area. Climate cooling and continuous fall of the sea level made the study area change from toe of slope-submarine plain to lower continental slope, middle continental slope and finally to upper continental slope, which in turn affected the strength of the gravity flow. The three times of tectonic uplifting and climate cooling in the West African coast provided abundant sediment supply for the development of gravity flow deposits. Multistage activities of salt structures played important roles in redirecting, restricting, blocking and destroying the gravity flow deposits. Clarifying the characteristics, evolution and controlling factors of the Miocene gravity flow deposits in the Lower Congo—Congo Fan Basin can provide reference for deep-water petroleum exploration in this basin.